Detection of a young stellar population in the background of open clusters in the third galactic quadrant - Carraro, Giovanni (2005)
We report the detection of a young stellar population (≤100 Myr) in the background of nine young open clusters belonging to a homogenous sample of 30 star clusters in the third Galactic quadrant (at 217° ≤ l ≤ 260°). Deep and accurate UBVRI photometry allows us to measure model-independent age and distance for the clusters and the background population with high confidence. This population is exactly the same population (the blue plume) recently detected in three intermediate-age open clusters and suggested to be a ≤1-2 Gyr old population belonging to the Canis Major (CMa) overdensity (Bellazzini et al.; Martinez-Delgado et al.). However, we find that the young population in those three clusters and in six clusters of our sample follows the pattern of the Norma-Cygnus spiral arm as defined by CO clouds remarkably well, while in the other three program clusters it lies in the Perseus arm. We finally provide one example (out of 21) of a cluster that does not show any background population, demonstrating that this population is not ubiquitous toward CMa.